Perancangan Antarmuka dan Pengalaman Pengguna Aplikasi ESSA Mobile PT. Terminal Teluk Lamong menggunakan Pendekatan Human-Centered Design - Yulius Natalis Ega Pratama; Buce Trias Hanggara; Intan Sartika Eris Maghfiroh (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2022)
PT. Terminal Teluk Lamong uses information technology in the form of Employee Self Service Application (ESSA), a web-based personnel information system will be developed further into ESSA Mobile by the end of 2022. Users of the website version of ESSA face various issues, according to interviewees, including limited accessibility, a difficult attendance process, stacked notifications, and information that is not provided in real time. This research aims to provide a user interface and interaction for ESSA Mobile that is more accessible, fits user needs, and addresses issues that users have had with the website version of ESSA. The output of this research is a high-fidelity prototype. Human-Centered Design (HCD) approach was used in designing the solution for this research. Evaluation for this research was done using usability testing to measure three aspects, namely effectiveness, efficiency, and user satisfaction, using the System Usability Scale (SUS). The results of the effectiveness test showed a value of 95% for organic employees and 100% for employee superiors and human capital. The results of the efficiency test showed a TBE value of 0,131 goals/sec and an ORE value of 92,43% for organic employees; a TBE value of 0,258 goals/sec and an ORE value of 100% for employee superiors; and a TBE value of 0,174 goals/sec and an ORE value of 100% for human capital. The results of the satisfaction test showed an acceptable and excellent SUS score of 80 for organic employees, 76,88 for employee superiors, and 74,17 for human capital. Based on the tests result, the solution designed is considered successful in meeting user needs.